Evidencing ((n-C4H9)4N)2[W6I14] red–NIR emission and singlet oxygen generation by two photon absorption. Issue 33 (24th March 2021) - Molard, Yann; Taupier, Gregory; Paofai, Serge; Cordier, Stéphane
Abstract : Two photon absorption induced NIR emission has been observed for the first time for octahedral transition metal clusters. Abstract : We report the first proof of the ability of octahedral tungsten clusters to emit red–NIR light and to produce singlet oxygen upon two-photon absorption, in solution and in the solid-state. Such discoveries open new perspectives for tungsten cluster compounds in several fields like optoelectronics, photodynamic therapy, and bioimaging.